Public Transmission, and Religious Symbolism in the British Women’s Suffrage Movement: The Cases of Emily Wilding Davison’s Funeral and the Pilgrimage of the National Union of Women’s Suffrage Societies - Chloé Clément (Cahiers Victoriens et Edouardiens)
This paper will focus on how the religious symbolism used in the British women’s suffrage movement was integrated, perceived, and received by studying two particular cases: the funeral of the suffragette Emily Wilding Davison and the Pilgrimage of the National Union of Women’s Suffrage Societies. As the movement progressed and public methods of transmission evolved, suffrage organisations found new means to justify their arguments and propaganda. Religious symbols and concepts gradually represented the movement. While most of the transmission first happened in the suffrage press, these suffrage processions progressively became political platforms to transmit a symbolism drawing mostly from Christian imagery. Whether it was by celebrating martyrdom and the self-sacrificing spirit of suffragettes or organising a suffragist Pilgrimage to illustrate the power constitutional methods could hold, processions and religious symbolism blended to integrate the transmission of secular organisations. Still, processes for using religious symbolism question the religious attitudes of suffrage organisations and members. Davison’s funeral brings forward the importance of suffragette martyrdom for the organisation’s propaganda and members’ understanding of militancy and martyrdom in light of their religious convictions. Archival sources on the NUWSS Pilgrimage account for the decision-making process to include religious symbolism in a five-week national march. These public processions demonstrate that the sacrifice, devotion, and courage of women for the same sacred political and spiritual purpose could function as internal and external incentives to further the movement. Yet, although suffrage organisations deemed their transmission successful, the added value of the religious symbolism they deployed was questioned by the general press. Redefinition of religious notions and symbols as well as contests over their meaning have to be studied to appreciate the reasons for their integration, transmission and debates surrounding their efficiency.